497 Clinical Presentation Prior to Idiopathic Hypersomnia Diagnosis Among US Adults: A Retrospective, Real-World Claims Analysis. (3rd May 2021) - Saad, Ragy; Ben-Joseph, Rami; Prince, Patricia; Stack, Catharine; Bujanover, Shay; Taylor, Ben
Abstract: Introduction: Idiopathic hypersomnia (IH) is a rare, serious central hypersomnolence disorder for which there are no FDA-approved medications available. A retrospective study was conducted to characterize newly diagnosed patients with IH in the United States. Here, we report morbidity and comorbidity claims prior to IH diagnosis. Methods: Claims from the IBM® MarketScan® database were analyzed between January 2014 and September 2019. The general population cohort included all adults with ≥12 months of continuous enrollment. From this population, a cohort with newly diagnosed IH was identified, defined as ≥2 claims with an IH diagnosis code ≥1 day and ≤180 days apart, and without an IH diagnosis in the 12 months prior to cohort entry. Patients without continuous medical/prescription coverage (enrollment gaps >30 days) in the 12 months prior to cohort entry were excluded. Claims with diagnoses for select morbid/comorbid conditions were identified from 12 months prior to cohort entry for the IH and general population cohorts and summarized using descriptive statistics. A sensitivity analysis was conducted on IH patients with the diagnosis code recorded in the primary position ("primary IH") on the claims to understand the effects of applying a more specific definition of IH. Results: Of the general population cohort (N=32, 948, 986; mean age, 42 years; 52% female), 4, 980 (0.015%) newly diagnosed IH patients were identified (mean age, 43 years; 67% female). Sleep-related morbidities in the 12 months prior to cohort entry included narcolepsy type 2 (17%/0.1%) and hypersomnia (10%/0.2%) for the IH/general population cohorts, respectively. Common comorbidities were sleep apnea (50%/4%), mood disorders (32%/8%), depressive disorders (31%/7%), anxiety disorders (31%/9%), hyperlipidemia (30%/20%), headache/migraine (24%/7%), diabetes or use of diabetes/obesity medication (20%/12%), hypertension (15%/10%), and cardiovascular disease (14%/8%) for the IH/general population cohorts, respectively. Common morbidities/comorbidities for the primary IH cohort (n=2, 205) were generally similar to the overall IH population. Conclusion: Compared with the general MarketScan® population, morbidities/comorbidities were more common for IH patients across all conditions analyzed, including sleep disorders and psychiatric, cardiometabolic, and cardiovascular disease. With cardiovascular risk factors common upon diagnosis of IH, therapies that do not increase cardiovascular risk are warranted. Support (if any): Jazz Pharmaceuticals